Executive functions in trauma-exposed youth: a meta-analysis - Rosanne Op den Kelder; Alithe L. Van den Akker; Hilde M. Geurts; Ramón J. L. Lindauer; Geertjan Overbeek (European Journal of Psychotraumatology, 2018)
An earlier meta-analysis and review indicated that trauma exposure may be related to lower levels of executive functioning in youth. Since different developmental trajectories were found for three core executive functions, the present study focused on working memory, inhibition, and cognitive flexibility specifically. We conducted a multi-level meta-analysis on 55 studies and 322 effect sizes published between 2001 and 2017 that were retrieved from MEDLINE, Embase, and PsycINFO. The 8070 participants in selected studies were aged 2–25 years. We investigated whether the association between constructs would be moderated by trauma-specific moderators (onset, duration, and type), and study (age, gender, ethnicity, and socio-economic status) and measurement (quality) characteristics. We found small to medium effect sizes for working memory (d = −0.49), inhibition (d = −0.46), and cognitive flexibility (d = −0.44). Moderator analyses showed that, for working memory, when studies used low-quality measurements the effect size was significantly stronger than when studies used high-quality measurements.Compared to single trauma-exposed youth, violence-exposed/abused and foster care/adopted youth showed more problems in inhibition, and foster care/adopted youth showed more problems in cognitive flexibility. Our findings imply that trauma-exposed youth have lower levels of executive functions. Clinical practice should incorporate problems in executive functioning, especially working memory, inhibition, and cognitive flexibility, in assessment and treatment guidelines.